Relasi Birokrat dan Politisi Dalam Pilkada Gubernur Sumatera Barat Tahun 2020 - Rika Yanita Susanti; Khairul Fahmi (Indonesian Journal of Religion and Society, 2022)
In electoral politics, the relationship between bureaucrats and politicians is increasingly obvious because the interests between the two meets at one point, namely power. As a result, ASN, which should be neutral in elections and elections, is drawn into the vortex of political currents, especially in the implementation of the Pilkada which is in direct contact with the interests of the bureaucrats and ASN. This phenomenon occurs in almost all of Indonesia during the Pilkada, especially since the candidate who is advancing is the incumbent candidate. This practice also occurred in the 2020 West Sumatra gubernatorial election. Bureaucrats became one of the supporters and loyalists (brokers) of the candidates who came forward. One of the pairs of candidates who have a lot of contact with these bureaucrats is the pair Mahyeldi-Audy. One of them is the appointment of three Padang City Government officials to become officials in the West Sumatra Provincial Government, although they have gone through the screening process, there are still allegations of remuneration for the contributions of the three bureaucrats in winning Mahyeldi-Audy. To analyze the problems above, the method used is a qualitative approach and the type of research used is a literature review. In this study, it is explained that in the process of selecting the governor, bureaucrats and PKS collaborate in collecting votes according to their respective duties. This collaboration was one of the decisive factors for Mahyeldi and PKS's victory in the West Sumatra gubernatorial election. the practice of political brokers and pig-barrel politics explains the relationship between bureaucrats and politicians. Bureaucrats who have a strong social network engine are able to get votes in their respective environments, especially those senior bureaucrats are community leaders who have supporters. Coupled with pragmatic politics that prioritizes money politics in elections, making these bureaucrats and politicians a force in the winning process.